(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article provides an in-depth analysis of the role and importance of small business and private entrepreneurship in ensuring employment in the Republic of Uzbekistan. The study reveals the role of this sector in creating new jobs, reducing unemployment, and expanding self-employment opportunities for the population. The article studies the impact of small business and private entrepreneurship on socio economic development based on statistical indicators, scientific sources, and regulatory legal acts. It also presents conclusions and practical proposals aimed at further increasing employment through the development of this sector.